Deconvoluting the Photonic and Electronic Response of 2D Materials: The Case of MoS2. Issue 1 (December 2017) - Zhang, Kehao; Borys, Nicholas; Bersch, Brian; Bhimanapati, Ganesh; Xu, Ke; Wang, Baoming; Wang, Ke; Labella, Michael; Williams, Teague; Haque, Md; Barnard, Edward; Fullerton-Shirey, Susan; et al.
Abstract Evaluating and tuning the properties of two-dimensional (2D) materials is a major focus of advancing 2D science and technology. While many claim that the photonic properties of a 2D layer provide evidence that the material is "high quality", this may not be true for electronic performance. In this work, we deconvolute the photonic and electronic response of synthetic monolayer molybdenum disulfide. We demonstrate that enhanced photoluminescence can be robustly engineered via the proper choice of substrate, where growth of MoS2 on r-plane sapphire can yield >100x enhancement in PL and carrier lifetime due to increased molybdenum-oxygen bonding compared to that of traditionally grown MoS2 on c-plane sapphire. These dramatic enhancements in optical properties are similar to those of super-acid treated MoS2, and suggest that the electronic properties of the MoS2 are also superior. However, a direct comparison of the charge transport properties indicates that the enhanced PL due to increased Mo-O bonding leads to p-type compensation doping, and is accompanied by a 2x degradation in transport properties compared to MoS2 grown on c-plane sapphire. This work provides a foundation for understanding the link between photonic and electronic performance of 2D semiconducting layers, and demonstrates that they are not always correlated.